CD4+ T cells are the major predictor of HCMV control in allogeneic stem cell transplant recipients on letermovir prophylaxis - Lauruschkat, Chris David; Muchsin, Ihsan; Rein, Alice; Erhard, Florian; Grathwohl, Denise; Dölken, Lars; Köchel, Carolin; Falk, Christine Susanne; Einsele, Hermann; Wurster, Sebastian; Grigoleit, Götz Ulrich; Kraus, Sabrina (Frontiers in Immunology, 2023)
Human cytomegalovirus (HCMV) causes significant morbidity and mortality in allogeneic stem cell transplant (alloSCT) recipients. Recently, antiviral letermovir prophylaxis during the first 100 days after alloSCT replaced PCR-guided preemptive therapy as the primary standard of care for HCMV reactivations. Here, we compared NK-cell and T-cell reconstitution in alloSCT recipients receiving preemptive therapy or letermovir prophylaxis in order to identify potential biomarkers predicting prolonged and symptomatic HCMV reactivation. To that end, the NK-cell and T-cell repertoire of alloSCT recipients managed with preemptive therapy (n=32) or letermovir prophylaxis (n=24) was characterized by flow cytometry on days +30, +60, +90 and +120 after alloSCT. Additionally, background-corrected HCMV-specific T-helper (CD4+IFNγ+) and cytotoxic (CD8+IFNγ+CD107a+) T cells were quantified after pp65 stimulation. Compared to preemptive therapy, letermovir prophylaxis prevented HCMV reactivation and decreased HCMV peak viral loads until days +120 and +365. Letermovir prophylaxis resulted in decreased T-cell numbers but increased NK-cell numbers. Interestingly, despite the inhibition of HCMV, we found high numbers of “memory-like” (CD56dimFcεRIγ- and/or CD159c+) NK cells and an expansion of HCMV-specific CD4+ and CD8+ T cells in letermovir recipients. We further compared immunological readouts in patients on letermovir prophylaxis with non/short-term HCMV reactivation (NSTR) and prolonged/symptomatic HCMV reactivation (long-term HCMV reactivation, LTR). Median HCMV-specific CD4+ T-cell frequencies were significantly higher in NSTR patients (day +60, 0.35 % vs. 0.00 % CD4+IFNγ+/CD4+ cells, p=0.018) than in patients with LTR, whereas patients with LTR had significantly higher median regulatory T-cell (Treg) frequencies (day +90, 2.2 % vs. 6.2 % CD4+CD25+CD127dim/CD4+ cells, p=0.019). ROC analysis confirmed low HCMV specific CD4+ (AUC on day +60: 0.813, p=0.019) and high Treg frequencies (AUC on day +90: 0.847, p=0.021) as significant predictors of prolonged and symptomatic HCMV reactivation. Taken together, letermovir prophylaxis delays HCMV reactivation and alters NK- and T-cell reconstitution. High numbers of HCMV-specific CD4+ T cells and low numbers of Tregs seem to be pivotal to suppress post-alloSCT HCMV reactivation during letermovir prophylaxis. Administration of more advanced immunoassays that include Treg signature cytokines might contribute to the identification of patients at high-risk for long-term and symptomatic HCMV reactivation who might benefit from prolonged administration of letermovir.